Biases in Retrospective Perceptions of Changes in Well-Being Associated With Aging Attitudes. (27th July 2022) - Hess, Thomas M; Park, Jeongsoo; Fung, Helene H; Rothermund, Klaus
Abstract: Objectives: Aging attitudes have important consequences on functioning in later life. A critical question concerns whether such attitudes may bias perceptions of one's own aging, with potentially negative effects on important outcomes. Methods: Using data from adults aged 30–85 years in Germany ( n = 623), Hong Kong ( n = 317), and the United States ( n = 313), we examined the impact of age and aging attitudes on accuracy of perceptions of change in well-being over 5 years in different domains of functioning. Results: Across contexts, comparisons revealed good correspondence between retrospective reports and actual change. However, older adults and those with negative attitudes retrospectively reported less positive change over this period. Inconsistent with expectations, attitudes did not consistently bias accuracy of retrospective reports over cultures and domains of functioning, nor did age have a consistent moderating effect on the impact of attitudes on accuracy. Discussion: The results highlight the complex relationship between various personal characteristics and perceptions of change in well-being, as well as the potentially insidious effects of attitudes on the accuracy of these perceptions.